Minimally symptomatic posterior reversible encephalopathy in Guillain-Barré syndrome - Piccolo, Giovanni (Funct Neurol, 2015)
Posterior reversible encephalopathy syndrome (PRES) is a rare occurrence in patients with Guillain-Barré syndrome (GBS). Two patients with neuroradiological evidence of PRES without central nervous system (CNS) symptoms were recently reported. We present the case of a GBS patient with minimal CNS symptoms and magnetic resonance imaging findings consistent with PRES. PRES in GBS might be an underestimated condition. It should be suspected in GBS patients in the presence of even mild CNS symptoms. A timely PRES diagnosis along with early correction of autonomic system dysfunction in GBS patients is recommended to prevent possible dangerous CNS complications.